MODAL SOSIAL PEMIMPIN ORGANISASI MAHASISWA DALAM MEMENANGKAN PEMILIIHAN RAYA MAHASISWA DI FKIP UNIVERSITAS SULTAN AGENG TIRTAYASA TAHUN 2022 - Putra, Teguh Pratama; Widiansyah, Subhan; Hardiansyah, Muhammad Agus (Universitas Pendidikan Ganesha, 2024)
The regeneration of student organization leaders in the Faculty of Teacher Training and Education is carried out once a year. Therefore, students who want to nominate themselves to become leaders of student organizations must have social capital, including networks, norms, and trust. This study describes what kind of social capital a student organization leader must have in winning the FKIP Untirta student election. This study used a qualitative approach through observation, interviews, and documentation. In this study there were 20 key informants, namely the head of the internal organization at FKIP Untirta, and 3 additional informants, namely FKIP Untirta students. The theory used is social capital theory from Robert Putnam which consists of networks, norms, and trust. The results of the study show that (1) the existing network is in the form of student participation in campus external organizations, relations with department friends, and faculty friends relations. (2) norms in the form of requirements or existing rules to be able to nominate themselves to become student organization leaders at FKIP Untirta, these rules are contained in the Faculty Regulations. (3) trust arises when students have successfully carried out a large work program and also an offer in the form of a vision-mission or excellent work program.